Hoechst 33342 Is a Hidden "Janus" amongst Substrates for the Multidrug Efflux Pump LmrP. - Arthur Neuberger; Hendrik W van Veen (PLoS ONE)
Multidrug transporters mediate the active extrusion of antibiotics and toxic ions from the cell. This reaction is thought to be based on a switch of the transporter between two conformational states, one in which the interior substrate binding cavity is available for substrate binding at the inside of the cell, and another in which the cavity is exposed to the outside of the cell to enable substrate release. Consistent with this model, cysteine cross-linking studies with the Major Facilitator Superfamily drug/proton antiporter LmrP from Lactococcus lactis demonstrated binding of transported benzalkonium to LmrP in its inward-facing state. The fluorescent dye Hoechst 33342 is a substrate for many multidrug transporters and is extruded by efflux pumps in microbial and mammalian cells. Surprisingly, and in contrast to other multidrug transporters, LmrP was found to actively accumulate, rather than extrude, Hoechst 33342 in lactococcal cells. Consistent with this observation, LmrP expression was associated with cellular sensitivity, rather than resistance to Hoechst 33342. Thus, we discovered a hidden "Janus" amongst LmrP substrates that is translocated in reverse direction across the membrane by binding to outward-facing LmrP followed by release from inward-facing LmrP. These findings are in agreement with distance measurements by electron paramagnetic resonance in which Hoechst 33342 binding was found to stabilize LmrP in its outward-facing conformation. Our data have important implications for the use of multidrug exporters in selective targeting of "Hoechst 33342-like" drugs to cells and tissues in which these transporters are expressed.